Measurements of transverse energy flow in deep-inelastic scattering at HERA - Adloff, C; Andreev, V; Andrieu, B; Arkadov, V; Astvatsatourov, A; Ayyaz, I; Babaev, A; Bahr, J; Baranov, P; Barrelet, E; Bartel, W; Bassler, U; et al. (2000)
Measurements of transverse energy flow are presented for nentral current deep-inelastic scattering events produced in positron-proton collisions at HERA. The kinematic range covers squared momentum transfers Q2 from 3.2 to 2200 GeV2, the Bjorken sealing variable cursive Greek chi from 8 · 10-5 to 0.11 and the hadronic mass W from 66 to 233 GeV. The transverse energy flow is measured in the hadronic centre of mass frame and is studied as a function of Q2. cursive Greek chi. W and pseudorapidity. A comparison is made with QCD-based models. The behaviour of the mean transverse energy in the central pseudorapidity region and an interval corresponding to the photon fragmentation region are analysed as a function of Q2 and W.